THU0559 IMPLEMENTATION OF A TRIAGE SYSTEM IN A HOSPITAL WITH HIGH DEMAND FOR CARE. (2nd June 2020) - Ibáñez, S.; Valenzuela, F.; Martinez, O.; Valenzuela, O.; Silva, F.; Villar, M. J.; Poblete, M. P.; Mardones, C.
Abstract : Background: Our hospital has 4 Rheumatologists and is in charge of 425.000 inhabitants (1 rheumatologist per 106.250 inhabitants). In November 2017, there were 503 referrals from primary care waiting for a first visit with the rheumatologist. Given the impossibility of covering this number of waiting patients through normal operation, it was decided to implement a rapid access polyclinic that started in December of 2017. Objectives: To evaluate the effectiveness of a triage system in a center with high demand for care. Methods: Patients referred by the general practitioner were evaluated by a senior rheumatologist in a 10-minute consultation using a predefined interrogation, expanded case-by-case based on the criteria of each rheumatologist. According to the results of the interview, the situation of the patient was categorized into: urgent, normal rheumatology control or control in primary care. For urgent consultations, an early control polyclinic was created to evaluate these patients within the following 15 days. The usual consultations entered into the usual scheduling system. The pathologies that were considered to require control in primary care were assigned to a coordination polyclinic where the patients were evaluated by an internist, in charge of confirming the diagnosis, educating the patient, and, if applicable, refer to primary care. No patient was discharged immediately after the triage. We report the data of the first 136 patients. Results: The waiting time was reduced from a median of 275 days (IQR 66-591) to 46.5 (23-140). Refer to table 1 for full results. In 52.2% of referred patients the suspicion of a chronic autoimmune or inflammatory disease was described in the referral note. In these patients, when comparing with patients whose referral notes did not refer to an inflammatory or autoimmune disease, the waiting time for triage was significantly shorter, the percentage of patients who were discharged from rheumatology was significantly lower, and the percentage of patients in whom a chronic autoimmune or inflammatory disease was confirmed in the first control was significantly higher. Conclusion: We consider this strategy as successful in reducing care times and identifying patients who require an early start of treatment and close control. Referral notes from primary care were generally adequate to identify patients who required to continue rheumatologist control. References: None. Disclosure of Interests: Sebastian Ibáñez Consultant of: Novartis, Paid instructor for: Bristol Myers, Speakers bureau: Abbvie, Francisca Valenzuela: None declared, Oriela Martinez: None declared, Omar Valenzuela Consultant of: Bristol Myers, Paid instructor for: Bristol Myers, Speakers bureau: Bristol Myers, Abbvie, Francisco Silva Consultant of: Roche, Speakers bureau: Roche, María José Villar: None declared, María Paz Poblete: None declared, Claudia Mardones: None declared